Access, adequacy and utilization of agricultural credit to farmers in Pakistan : the case of Mardan District, Khyber Pakhtunkhwa - Saqib, Shahab E.; Ahmad, Mokbul Morshed; Soparth Pongquan; Thapa, Gopal B.; Higher Education Commission (HEC) Pakistan; Asian Institute of Technology Fellowship (Pathum Thani : Asian Institute of Technology, 2015)
The research study has tried to analyze the farmer{u2019}s access to agricultural credit, their credit adequacy and utilization. The utilization is studied in agriculture and non-agriculture aspects. This research has focused on the most vulnerable farmers in the district Mardan, which were in more need of credit. The general objective of this research was to analyze the farmer{u2019}s access to credit sources in flood disaster prone area. The specific objectives were to analyze the farmer{u2019}s access to credit sources that are divided into two categories, small farmers and medium & large farmers, to know about their adequacy and further utilization in different needs. The research was an explanatory and evaluation mix type of research. It is basically a primary research applying quantitative techniques. The major tools used for collection of data were;standardized questionnaire survey combined with checklist.Study evaluated the farmers{u2019}access and adequacy of credit and made an effort to link with socioeconomic factors. The study employed, chi-square, T-Tests and F-Tests to see the differentiation among the farmers groups. Bi-variate analysis was used quantitative approach to find the association between dependent variables with independent variables. Results showed that most of the large farmers had accessed formal sources for credit,while small farmers were found to have limited access. Small farmers were more relied on informal sources among that, relatives were the most important. A significant difference was observed in small farmers and medium and large farmers in their average amount of credit taken from formal sources and total credit amount. Small farmers{u2019}credit access ratio was found lower in case of formal sources and was above in the case of informal sources from average access ratio. While the results were opposite for medium and large farmers they had more than average access from formal sources and lower in the case of informal sources. Medium and large farmers were found more credit adequate than small farmers. More credit fungibility and less investment in agriculture was found more among the small farmers compared with medium and large farmers. Most of the small farmers used the credit in domestic needs,while medium and large farmers used credit in establishing businesses for the purpose of income diversification. Among the socioeconomic factors affecting farmer{u2019}s access to agricultural credit and their credit adequacy many factors were found significant. For this purpose the Bi-variate analysis was employed in three groups separately, like for small farmers, medium and large farmers, and overall all farmers. Age, education, total landholding, proportion of own land, land ownership were the positively and significantly affecting factors in farmers access to credit and their credit adequacy. Household size were significant in case of farmers access to credit, however,were found insignificant in case of adequacy of credit. Experience, distance from the river, total income and farm labour had shown ambiguous results, in some cases were found significant but in other case were insignificant. A set of recommendations were forwarded for improvement in the credit policy, to enhance the production and income level of farmers in general and small farmers in particular.
A research submitted in partial fulfillment of the requirements for the degree of Master of Science in Regional and Rural Development Planning
Research studies project report (M. Sc.) - Asian Institute of Technology, 2015
Keywords: Agricultural credit -- Pakistan